2016
DOI: 10.1007/s00432-016-2147-y
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised analysis reveals two molecular subgroups of serous ovarian cancer with distinct gene expression profiles and survival

Abstract: did not derive from high-versus low-grade serous carcinomas and were unrelated to histological (ovarian vs. fallopian) origin. Interestingly, there was considerable overlap between identified prognostic signature and a recently described invasion-associated signature related to stromal desmoplastic reaction. Several genes from this signature were validated by quantitative PCR; two of them-DSPG3 and LOX-were validated both in the initial and independent sets of samples and were significantly associated with OS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 29 publications
2
35
0
Order By: Relevance
“…Fifteen of the 21 DEGs in BMets are ECM-related genes (Table S8). Whereas 13 of the 21 genes are reportedly expressed exclusively in the stroma [5,[21][22][23][24][25][26][27][28][29][30][31][32], we have determined that LRRC15 is expressed in both the stroma and the epithelial compartment ( Fig. 3).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Fifteen of the 21 DEGs in BMets are ECM-related genes (Table S8). Whereas 13 of the 21 genes are reportedly expressed exclusively in the stroma [5,[21][22][23][24][25][26][27][28][29][30][31][32], we have determined that LRRC15 is expressed in both the stroma and the epithelial compartment ( Fig. 3).…”
Section: Discussionmentioning
confidence: 83%
“…This may suggest that BMet-upregulated genes are more immediately associated with surgical outcomes and intra-abdominal extension of cancer, whereas survival associations are most likely mediated by surgical results (RD0 vs non-RD0). Interestingly, Lisowska et al [24], reported EPYC (DSPG3) as 1 of 2 genes (along with LOX) significantly associated with overall survival and disease-free survival in OC.…”
Section: Discussionmentioning
confidence: 99%
“…GSE63885, based on the GPL570 platform (HG-U133_Plus_2; Affymetrix Human Genome U133 Plus 2.0 Array), contained 70 serous and 5 nonserous OC samples with complete clinical data [20]. All gene expression data were subjected to log2 transformation.…”
Section: Geo Dataset Acquirementmentioning
confidence: 99%
“…Importantly, due to the lack of speci c symptoms, the majority of OC patients often go undetected until the tumor has spread into the pelvic cavity or has invaded adjacent organs with nearly 60% of patients being diagnosed at advanced clinic stages since their rst doctor visit [2]. The clinicopathological features of OC that are correlated with a poor prognosis, include advanced stage, incomplete surgery, residual volume after surgery, and tumor histological type [3][4][5]. Despite the new emerging strategies targeting OC, recurrence still remains the most critical threat to the long-term survival of OC patients.…”
Section: Introductionmentioning
confidence: 99%